Odpowiedź :
Odpowiedź:
[tex]a)\ \ \dfrac{\frac{2}{4}+\frac{1}{6}}{\frac{2}{5}-\frac{1}{2}}+(3\frac{2}{18}-4\frac{6}{13})\cdot(0,75-\frac{3}{4})=\dfrac{\frac{1}{2}+\frac{1}{6}}{\frac{4}{10}-\frac{5}{10}}+(3\frac{1}{9}-4\frac{6}{13})\cdot(\frac{3}{4}-\frac{3}{4})=\\\\\\=\dfrac{\frac{3}{6}+\frac{1}{6}}{-\frac{1}{10}}+(3\frac{1}{9}-4\frac{6}{13})\cdot0=\dfrac{\frac{4}{6}}{-\frac{1}{10}}+0=\frac{4}{6}:(-\frac{1}{10})=\frac{2}{3}\cdot(-10)=-\frac{20}{3}=-6\frac{2}{3}[/tex]
[tex]b)\ \ \frac{3}{5}-(1,4\cdot\frac{5}{14}-\frac{0,9}{3^2}):(-\frac{1}{5})=\frac{3}{5}-(\frac{\not14^1}{\not10_{2}}\cdot\frac{\not5^1}{\not14_{1}}-\frac{0,9}{9}):(-\frac{1}{5})=\\\\=\frac{3}{5}-(\frac{1}{2}-0,1):(-\frac{1}{5})=\frac{3}{5}-(0,5-0,1):(-\frac{1}{5})=\frac{3}{5}-0,4\cdot(-5)=\frac{3}{5}+2=2\frac{3}{5}[/tex]
[tex]c)\ \ \frac{2}{3}-[0,8\cdot\frac{3}{(-2)^2}-\frac{(-2)^2}{5}]:(-1\frac{1}{2})=\frac{2}{3}-(\frac{8}{10}\cdot\frac{3}{4}-\frac{4}{5}):(-\frac{3}{2})=\\\\=\frac{2}{3}-(\frac{\not4}{5}\cdot\frac{3}{\not4}-\frac{4}{5}):(-\frac{3}{2})=\frac{2}{3}-(\frac{3}{5}-\frac{4}{5})\cdot(-\frac{2}{3})=\frac{2}{3}-(-\frac{1}{5})\cdot(-\frac{2}{3})=\frac{2}{3}-\frac{2}{15}=\\\\=\frac{10}{15}-\frac{2}{15}=\frac{8}{15}[/tex]
[tex]d)\ \ \dfrac{5\frac{3}{4}-8\frac{1}{3}}{\frac{1}{2}-(\frac{2}{3})^2}-\frac{2}{3}:(-\frac{4}{27})=\dfrac{\frac{23}{4}-\frac{25}{3}}{\frac{1}{2}-\frac{4}{9}}-\frac{2}{3}:(-\frac{4}{27})=\dfrac{\frac{69}{12}-\frac{100}{12}}{\frac{9}{18}-\frac{8}{18}}-\frac{\not2^1}{\not3_{1}}\cdot(-\frac{\not27^9}{\not4_{2}})=\\\\\\=\dfrac{-\frac{31}{12}}{\frac{1}{18}}+\frac{9}{2}=-\frac{31}{12}:\frac{1}{18}+\frac{9}{2}=-\frac{31}{\not12_{2}}\cdot\not18^3+\frac{9}{2}=-\frac{31}{2}\cdot3+\frac{9}{2}=[/tex]
[tex]=-\frac{93}{2}+\frac{9}{2}=-\frac{84}{2}=-42\\\\\\e)\ \ (\frac{1}{3}-\frac{1}{2}):(\frac{5}{3}-\frac{5}{4})-(0,25-\frac{3}{5}:0,625)=(\frac{2}{6}-\frac{3}{6}):(\frac{20}{12}-\frac{15}{12})-(\frac{25}{100}-\frac{3}{5}:\frac{625}{1000})=\\\\=-\frac{1}{6}:\frac{5}{12}-(\frac{1}{4}-\frac{3}{5}:\frac{5}{8})=-\frac{1}{\not6_{1}}\cdot\frac{\not12^2}{5}-(\frac{1}{4}-\frac{3}{5}\cdot\frac{8}{5})=-\frac{2}{5}-(\frac{1}{4}-\frac{24}{25})=[/tex][tex]=-\frac{2}{5}-(\frac{25}{100}-\frac{96}{100})=-\frac{2}{5}-(-\frac{71}{100})=-\frac{2}{5}+\frac{71}{100}=-\frac{40}{100}+\frac{71}{100}=\frac{31}{100}[/tex]
[tex]f)\ \ \frac{4}{5}:(\frac{1}{2}-\frac{1}{5})-(\frac{2}{3}-(\frac{3}{8}-1\frac{1}{3}))=\frac{4}{5}:(\frac{5}{10}-\frac{2}{10})-(\frac{2}{3}-(\frac{3}{8}-\frac{4}{3}))=\\\\=\frac{4}{5}:\frac{3}{10}-(\frac{2}{3}-(\frac{9}{24}-\frac{32}{24}))=\frac{4}{\not5_{1}}\cdot\frac{\not10^2}{3}-(\frac{2}{3}-(-\frac{23}{24}))=\frac{8}{3}-(\frac{2}{3}+\frac{23}{24})=[/tex]
[tex]=\frac{8}{3}-(\frac{16}{24}+\frac{23}{24})=\frac{8}{3}-\frac{39}{24}=\frac{8}{3}-\frac{13}{8}=\frac{64}{24}-\frac{39}{24}=\frac{25}{24}=1\frac{1}{24}[/tex]